Neutropenia management in patients receiving myelosuppressive polychemotherapy for early breast cancer in Belgium: BRONS study results. Issue 2 (3rd March 2020) - Catala, Gaetan; Mebis, Jeroen; Jerusalem, Guy; Verhoeven, Didier; Awada, Ahmad; Bols, Alain; Somers, Luc; Van Den Broeck, Anke; Duhoux, Francois P; Machiels, Jean-Pascal
ABSTRACT: Background : Chemotherapy plays an important role in the treatment of early breast cancer (EBC). Granulocyte-colony stimulating factors (G-CSF) can reduce the risk of febrile neutropenia as primary prophylaxis (PP) or secondary prophylaxis (SP). The BRONS study investigated the incidence of serious neutropenic events (SNE) and G-CSF use in a Belgian population of EBC patients treated with myelosuppressive polychemotherapy. Methods : Conducted in 2011, this study was a prospective, multicentre, observational trial involving 260 patients. The primary endpoint was the incidence of SNE defined as either febrile neutropenia (FN) or prolonged severe neutropenia (PSN; neutrophil count ≤0.5 × 10⁹ for at least five days). Secondary endpoints included a description of the chemotherapeutic regimens prescribed and G-CSF use. Results : Nine percent of patients were treated with a dose-dense regimen (DD) and 91% received classical chemotherapy (CC). PP with G-CSF (PPG) was given to 20% of patients (100% in DD and 11% in CC). Eighteen percent of patients presented a SNE (4% in DD and 20% in CC) of which 15% were FN and 3% PSN. SNE occurrence was 8% in the PPG subgroup and 21% in the no-PPG subgroup. In the DD subgroup, all patients received PPG and no FN was reported. Twenty six adverse events related to G-CSF were reported in 8.2% of patients and two of these were classified as severe. Conclusion : This observational study highlights the high incidence of SNE with CC regimens in patients who do not receive PPG. It also confirms the safe profile of DD regimens with G-CSF support.